Análisis para la integración de imágenes obtenidas por la tomografía axial computarizada y la resonancia magnética. - López, Meisbel Daudinot; Sardina, Yoander Estrada (MEDISAN, 2016)
The medical images integration is the process of register and fuse them with the purpose of getting a higher quantity of diagnostic information. In this work an analysis for images integration obtained through the computerized axial tomography and the magnetic resonance is carried out, for which a tool in the Matlab program was developed, where the registration by means of equivalent characteristic is implemented; also, the couples of images are compared by several fusion rules, aimed at identifying the best algorithm in which the resulting image fused contains the highest quantity of information of the original representations.